Case Report: Molecular Profiling Assists in the Diagnosis and Treatment of Cancer of Unknown Primary - Yu, Bo; Wang, Qifeng; Liu, Xin; Hu, Silong; Zhou, Liangping; Xu, Qinghua; Sun, Yifeng; Hu, Xichun; Luo, Zhiguo; Zhang, Xiaowei (Frontiers in Oncology, 2022)
Background: For cancer of unknown primary (CUP), non-selective empiric chemotherapy is usually used. However, patients suffering from CUP are generally assumed to have a dismal prognosis with median overall survival of less than one year. Therefore, clinicians eagerly await the establishment of effective strategies for diagnosis and treatment. In recent years, the remarkable advances in next-generation sequencing (NGS) technology have enabled the wide usage of DNA/RNA sequencing to comprehensively analyze the molecular information of individual tumors and identify potential targets for patients’ diagnosis and treatment. Here, we describe a patient of CUP who was successfully diagnosed and treated with targeted therapy directed by comprehensive molecular profiling. Case presentation: A 61-year-old Asian woman with a painless, slow-growing mass lesion in the mesosternum underwent fluorodeoxyglucose-positron emission tomography/computed tomography, who was found malignant metastatic tumors in the mesosternum. Conventional pathological examination of metastatic lesions could not conclude the primary origin of the tumors. The patient was diagnosed with CUP at first. Then comprehensive molecular profiling was employed to identify the tumor origin and genetic alterations. A gene expression-based tissue origin assay was performed using a tissue biopsy sample. The test result suggested that the lesion tumors might be breast cancer metastasis. Furthermore, liquid biopsy-based circulating tumor DNA profiling detected an ERBB2 copy number amplification. Subsequent surgery and additional postoperative pathology analysis confirmed that the primary tumor site was indeed located in the right outer upper quadrant of the breast. After local surgical resection, the patient received 8 cycles of TCbHP chemotherapy with subsequent HER2 targeted maintenance therapy. Currently, the patient is on regular follow-up and has achieved disease control for up to 6 months. Conclusion: Our findings suggest that molecular identification of the tumor origin and the detection of actionable molecular alterations may offer promise for improved diagnostic accuracy and important therapeutic implications for patients with the CUP syndrome.